French team demonstrates terahertz transistor. - Hellemans, A. (IEEE spectrum)
The creation of a nanotransistor that generates a terahertz signal by means of plasma waves was reported by researchers in France in the 29 March issue of Applied Physics Letters. Such devices could fill a gap between 0.3 and 3 terahertz, for which no compact solid-state sources are available.